2022
DOI: 10.1111/wre.12525
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the emergence of Echinochloa crus‐galli populations in different locations. Part I: Variations in emergence timing and behaviour of two populations

Abstract: Echinochloa crus-galli (L.) P. Beauv. is one of the most important weeds. It is distributed worldwide and has adapted to diverse habitats and climatic conditions. This study aimed to compare the emergence patterns of two populations of E. crus-galli from different environments at 11 locations across Europe and the Middle East. Seeds of the two populations were collected from maize in Italy and from spring barley in Norway and were then buried in soil in autumn 2015. In the spring of 2016, the soil was disturbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“… Climate classification according to the updated Köppen–Geiger classification (Kottek et al, 2006): Cfa, temperate with no dry season, hot summer; Cfb, temperate with no dry season, warm summer; Csa, temperate with dry and hot summer (warm Mediterranean); Dfb, cold with no dry season and warm summer (continental). For specific climatic conditions of the experimental seasons (2015–16 and 2016–17), see Royo‐Esnal et al (2022). …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“… Climate classification according to the updated Köppen–Geiger classification (Kottek et al, 2006): Cfa, temperate with no dry season, hot summer; Cfb, temperate with no dry season, warm summer; Csa, temperate with dry and hot summer (warm Mediterranean); Dfb, cold with no dry season and warm summer (continental). For specific climatic conditions of the experimental seasons (2015–16 and 2016–17), see Royo‐Esnal et al (2022). …”
Section: Methodsmentioning
confidence: 99%
“…With this background, the Working Group on Germination and Early Growth (WG‐GEG) of the European Weed Research Society (EWRS) studied the emergence of two populations of E. crus‐galli , one from Italy and the other from Norway, at 12 locations in Europe and the Middle East (Royo‐Esnal et al, 2022). In that research, the population from Norway (NO) showed higher emergence at higher latitudes and lower emergence at lower latitudes, compared with the Italian population (IT).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations